Multisensory experiences in museums - Martins, Cláudia (2020)
Accessibility in cultural spaces comes across a myriad of barriers, which prevent people with impairments to fully enjoy these venues, such as galleries and museums, the cinema, the theatre, the stadium, the church or the graveyard, among others. Attempts to overcome these obstacles to social inclusion have been developed in the past decades with considerable progress in the US, the UK and a handful of European countries. Portugal is not yet among these countries, though some experiments have been carried out in terms of sensory accessibility. It is worth mentioning the Museu da Comunidade Concelhia da Batalha (Museum of the Community of Batalha) and Museu Nacional do Azulejo (National Museum of Tile) as Portuguese hallmarks for the access for all. My PhD research project focused on the analysis of the accessibility conditions of 20 cultural institutions which offered audioguides. Concurrently, I also examined the commentaries comprising their audioguides. Both stages of analysis followed technical, institutional, macrostructural and content-oriented criteria, centred on the elements that should be found in the audioguide structure and in the commentaries so that they could cater for the needs of people with sensory impairments, particularly the blind and visually-impaired. By drawing on some examples collected from the abovementioned research project, I aim at providing an insight into museum accessibility in Portugal and putting forth recommendations for best practices within museums, taking into account the urgent need to engage the various senses in cultural experiences.